1982
DOI: 10.1128/aac.22.3.513
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibilities of Aeromonas hydrophila against new antibiotics

Abstract: The antibiotic susceptibilities of 16 clinical isolates of Aeromonas hydrophila obtained from cancer patients with septicemia were studied. Of the new 1-lactam antibiotics tested, azthreonam and moxalactam were the most active, followed by cefoperazone, cefotaxime, and ceftizoxime. Excellent activity was demonstrated by chloroamphenicol, tetracycline, aminoglycosides, and trimethoprim-sulfamethoxazole. Semisynthetic penicillins had no appreciable activity against this organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
15
3
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 6 publications
3
15
3
1
Order By: Relevance
“…are generally self-limiting, but antimicrobial treat-ment may be necessary in serious infections, particularly systemic infection in immunocompromised patients. The antimicrobial susceptibility patterns observed in strains isolated in Saudi Arabia were similar to those reported from Great Britain, Canada and the United States of America (Smith, 1980;Fainstein et al, 1982;Gray, 1984). Most strains were resistant to broad-spectrum penicillins and many were also resistant to cefuroxime and cefoxitin.…”
Section: Discussionsupporting
confidence: 62%
“…are generally self-limiting, but antimicrobial treat-ment may be necessary in serious infections, particularly systemic infection in immunocompromised patients. The antimicrobial susceptibility patterns observed in strains isolated in Saudi Arabia were similar to those reported from Great Britain, Canada and the United States of America (Smith, 1980;Fainstein et al, 1982;Gray, 1984). Most strains were resistant to broad-spectrum penicillins and many were also resistant to cefuroxime and cefoxitin.…”
Section: Discussionsupporting
confidence: 62%
“…schubertii was resistant to trimethoprim and ampicillin, moderately susceptible to tobramycin, and susceptible to all of the other 19 antimicrobial agents tested. The present study has shown that strains from the tropics of Queensland are similar in their susceptibility patterns to Aeromonas strains from the temperate climes of Europe and the United States for the aminoglycosides, the broad-spectrum cephalosporins, the quinolones, the ureidopenicillins, tetracycline, chloramphenicol, aztreonam, cephalothin, and ampicillin (2,4,5,10,14,18). The antibiogram of the single northern Queensland strain ofA.…”
mentioning
confidence: 99%
“…Until recently, antimicrobial susceptibility studies of motile aeromonads have been undertaken with isolates simply specified as Aeromonas hydrophila (4,5,14). Because various infective processes and virulence factors correlate with different Aeromonas species, later studies have investigated the antimicrobial susceptibility of each of the three Aeromonas species to assist clinical management (2,10).…”
mentioning
confidence: 99%
“…are contradictory (1, 2, 5, 6, 13); nonetheless, some investigators have isolated these microorganisms more frequently from patients with diarrhea than from asymptomatic controls (1,2,6). Earlier studies (1,3,4) have identified Aeromonas isolates as Aeromonas hydrophila collectively. More recent data make a distinction between the three currently recognized Aeromonas species, namely A. caviae, A. hydrophila and A. sobria (9,11,13 (4,9,12).…”
mentioning
confidence: 99%